KEPEMIMPINAN KOLABORATIF KEPALA SEKOLAH TERHADAP KUALITAS PENDIDIKAN DI SEKOLAH DASAR - Arta Mulya Budi Harsono; Ahmad Suriansyah; Mahdalina Mahdalina (PT. Intelek Cendikiawan Nusantara, 2025)
The quality of education is influenced by the principal's ability to build a collaborative culture and a conducive learning environment. This study aims to describe the collaborative leadership practices of the principal and their impact on the quality of education at SDN Mawar 7 Banjarmasin. This study was conducted because collaborative leadership by the principal can improve school quality, but in-depth studies on the context of elementary schools in South Kalimantan are still very limited. This study uses qualitative methodology with an exploratory case study in an elementary school in the city of Banjarmasin. Information was collected through semi-structured interviews, non-participatory observation, and document analysis, with a focus on two teachers as the main subjects. This study states that the principal exercises a collaborative leadership style through two-way communication, decision-making through deliberation, teacher empowerment based on expertise or ability, continuous supervision, and the provision of innovative learning facilities. This collaborative leadership has a positive impact on improving the quality of learning, a collaborative school environment, and increasing teacher professionalism. In this study, collaborative leadership contributes significantly to the quality of education in elementary schools. These findings have important implications for the development of principal leadership practices and the strengthening of a collaborative culture in elementary schools.